Differential Impact of the Khatanga and Lena (Laptev Sea) Runoff on the Distribution and Grazing of Zooplankton - Pasternak, Anna; Drits, Alexander; Arashkevich, Elena; Flint, Mikhail (Frontiers in Marine Science, 2022)
The ecosystems of the Arctic Ocean and their expected changes in a context of Global climate processes are crucially dependent on the freshwater input. The freshwater signal is assumed to be the main structuring factor for the marine fauna on the shallow shelf of the Siberian Arctic seas. The Laptev Sea, as a part of the world’s widest continental shelves surrounding the Arctic Ocean, is a key area for understanding the land–ocean interaction in high latitude regions. The largest freshwater input is provided by the deltaic Lena river followed by the estuarine Khatanga river. The plumes of these rivers differ considerably in their hydrophysical characteristics, suggesting differential impacts on ecosystems of the adjacent shelf. The key component of pelagic ecosystems is zooplankton, which transfers energy from primary producers to higher trophic levels and modifies sedimentations processes. This study is focused on the influence of river discharge on zooplankton in the Laptev Sea at the end of productive season. We studied zooplankton biomass, species composition, distribution patterns of the dominant species and assessed herbivorous feeding rates and grazing pressure of these species along a transect from the inner Khatanga Gulf northward to the continental slope, and a transect in the Lena plume influenced area in August-September 2017. Despite large spatial extension of the Khatanga plume, the impact of river discharge on zooplankton species composition was restricted mainly to the inner Gulf where the brackish species shaped the community. Contrary to the Khatanga input, the Lena freshwater inflow was highly variable and under certain conditions (discharge rate, wind forcing) governed the structure of zooplankton community over a vast shelf area. Distribution patterns of zooplankton biomass, ingestion rates and grazing impact of the dominant species on phytoplankton over the shelf influenced by the Khatanga and Lena plumes were similar. Analysis of our results on demographic structure of Calanus glacialis suggests that seasonal development of the population was largely controlled by the time of ice retreat. Observed climatic changes in the Arctic were not reflected in the total zooplankton biomass and composition of the dominant species.